How to do things with dead people history, technology, and temporality from Shakespeare to Warhol - Dailey, Alice (Cornell University Press, 2022)
"This book studies Shakespeare's English history plays, contextualizing them among reproductive mechanisms and representational media spanning several centuries. It explores the plays' affinity with a transhistorical array of technologies for producing, reproducing, and interacting with dead things-technologies like photography, ventriloquist puppetry, X-ray imaging, capital punishment machines, and cloning."--